BASED ON THE FINITE ELEMENT ANALYSIS OF THE TWO PILLAR TESTER APPLICATION RESEARCH - LIU AiGuo; WANG Yang; CAI Peng; HOU ChaoJie; LIU ZhiCheng; LI ChangJie (Jixie qiangdu, 2016)
Gantry crane girder structure testing systems can be measured with the deflection of main beam with different structures in the same test environment. At first,through the finite element analysis,the four-pillar tester couldn’t meet the requirements of the large span bending test,Thus,through the finite element simulation,two pillar tester can meet the test requirements,Besides,the use of reinforced concrete structures constitute a closed since the reaction force loading system with the load frame steel structure,instead of the traditional steel structure used in the large span bending test. Finally,compared with the selection of four column structure,the advantages of the two column structure with reinforced concrete structure are given in equipment costs,installation and debugging.